Concurrent chemoradiotherapy versus induction chemotherapy followed by chemoradiotherapy (sequential approach) in the management of head and neck cancer. Issue 9 (September 2013) - Fabregas, Jesus C; Loaiza-Bonilla, Arturo; Talebi, Toni N; Warsch, Sean; Fernandez, Gustavo; Raez, Luis E; Santos, Edgardo S
Concurrent chemoradiation is considered the standard-of-care for locally advanced head and neck cancer of the hypopharynx, oropharynx and larynx, as well as unresectable disease. This paradigm was challenged by the introduction of induction chemotherapy (IC), which demonstrated non-inferiority in regards of overall survival (OS), along with increased organ preservation, when compared to the surgery and radiotherapy. More recently, IC followed by concurrent chemoradiation, the so-called sequential approach was developed in an attempt to decrease metastatic spread and improve locoregional control (LRC) rates, with much controversy amongst experts. A careful evaluation by a multidisciplinary team is necessary to recognize which patients should be offered this therapeutic approach due to a significantly greater rate of toxicity. Herein, we analyze the most current available evidence regarding the use of sequential therapy versus concurrent chemoradiation. Different factors including toxicity profile, adherence and patient characteristics play a major role in choosing the most appropriate treatment regimen.